P-001 Initial Multicentre Clinical Experience with Treating Small Aneurysms (<5mm) with the Penumbra PC400 Large Volume Coil: Improving the Treatment of Small Aneurysms at 4 High Volume US Centres. (14th July 2013) - Baxter, B; Quarfordt, S; Patel, A; Moyle, H; Turk, A; Chaudry, I; Turner, R; Frei, D; Huddle, D; Bellon, R
Abstract : Introduction/Purpose: We report clinical experience and long-term follow-up results in treating 24 small aneurysms in 22 patients, ranging from 2mm to 4.4mm, using the Penumbra PC400 Large Volume Coil at 4 high volume centres. Follow-ups are available for 12 aneurysms at the current time. Materials and Methods: Our treatment population consisted of 24 aneurysms ranging between 2 mm and 4.4 mm as measured by maximal aneurysm dimension, treated between February 2011 and September 2012. Seven were ruptured and 17 unruptured. Aneurysm location was 19 in the anterior circulation and 5 in the posterior circulation. Results: The average aneurysm size was 3.5 mm, with 52% average packing density. All aneurysms were treated entirely with PC400 coils, several with only 1 coil each. Fifty percent (50%) of the cases achieved an initial Raymond Scale of 1, 21% achieved a Raymond scale of 2, and 29% were Raymond Scale of 3. Half (12) of the aneurysms have angiographic follow-up at the time of this abstract. Based on the same/better/worse scale, 100% of aneurysms showed stable or improved angiographic outcomes at 6 months and one year. Seven had improved occlusion rating, and all the rest remained unchanged. We experienced a 0% overall rate of morbidity and mortality. One SAH patient had a thromboembolic event with no clinical sequelae, and 2 aneurysms had coil loop prolapse with no clinical sequelae, both patients being discharged with mRS 0. We continue to use the coils and accrue follow up and will update results at the time of the meeting. Conclusion: Our clinical experience with the PC400 Coil system has demonstrated this .020" coil and 025 ID deployment catheter to be safe and efficacious in treating small aneurysms. Use of the PC400 Large Volume Coil results in high packing densities and high rates of occlusion on follow-up. The softness profile of this large volume coil can allow treatment of small aneurysms in some cases with only 1 coil, and the improved body of the deployment catheter has markedly improved the treatment of small aneurysms and perhaps made it safer. Disclosures: B. Baxter: 3; C; Penumbra, Inc. S. Quarfordt: None. A. Patel: 3; C; Penumbra, Inc. H. Moyle: None. A. Turk: 3; C; Penumbra, Inc. I. Chaudry: 3; C; Penumbra, Inc. R. Turner: None. D. Frei: 3; C; Penumbra, Inc. D. Huddle: None. R. Bellon: None.